Primary endometrial squamous cell carcinoma (PESCC): Review of the literature and case report - Kuang-Han Liu; Chia-Chin Tsai; Krystal Baysan Lin; Pei-Shen Huang (Taiwanese Journal of Obstetrics & Gynecology)
Abstracts: Objective: Primary endometrial squamous cell carcinoma (PESCC) is an extremely rare type of endometrial cancer with limited research and understanding. This report presents a case of PESCC and reviews 37 cases from 1997. Case report: A 61-year-old menopausal woman presented with abnormal vaginal bleeding. Despite no prior Papanicolaou smears and normal Pap results this time, transvaginal sonography revealed 7 mm endometrial thickening and elevated cancer antigen 125 (CA-125). Dilatation and curettage revealed atypical glands with squamous metaplasia. On May 3, 2017, she underwent robot-assisted staging surgery (stage IB) and pelvic radiotherapy. No disease recurrence observed till now. Conclusion: Early diagnosis of PESCC is crucial for management. Although guidelines are lacking due to the rarity of PESCC, increased reporting and research are expected to shed light on this condition and facilitate the establishment of treatment protocols.